Analisis Nilai Bahasa dan Keagamaan dalam Pertunjukkan Wayang Kulit sebagai Seni Tradisional Jawa di Kabupaten Tegal - Lyswidia Andriansih; Aulia Rahmawati; Nisa Latifaturrafiqah; Indah Afra; Tiara Shifa (Fakultas Ilmu Tarbiyah dan Keguruan, Institut Agama Islam Bakti Negara Tegal, 2026)
Wayang art is one of the cultural heritages of the Indonesian archipelago that remains highly popular in various regions of Indonesia. In the Tegalan area, people are more familiar with and frequently use wayang santri rather than traditional shadow puppetry (wayang kulit), although both contain profound moral values, cultural messages, and meanings of life. This study aims to analyze the linguistic and religious values contained in wayang kulit performances as a medium of Islamic preaching within the Tegalan community. The research employed a descriptive qualitative method with cultural and religious approaches. Data were collected through observation, interviews, and documentation involving artists and local community members. The results show that wayang performances contain linguistic values in the form of symbols, expressions, and moral messages that are easily understood by society. In addition, the religious values embedded in the performances function as a medium of da’wah that encourages people to follow Islamic teachings and apply good morals in daily life. Although the Tegalan community more commonly uses wayang santri in events such as celebrations and Islamic religious commemorations, the educational and religious values in wayang performances still play an important role in character building and cultural preservation. Therefore, society can adopt the positive lessons and values contained in the performances as guidance for a better and more virtuous life.